2011
DOI: 10.1111/j.1467-7652.2011.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of OsPIN2 leads to increased tiller numbers, angle and shorter plant height through suppression of OsLAZY1

Abstract: SummaryCrop architecture parameters such as tiller number, angle and plant height are important agronomic traits that have been considered for breeding programmes. Auxin distribution within the plant has long been recognized to alter architecture. The rice (Oryza sativa L.) genome contains 12 putative PIN genes encoding auxin efflux transporters, including four PIN1 and one PIN2 genes. Here, we report that over-expression of OsPIN2 through a transgenic approach in rice (Japonica cv. Nipponbare) led to a shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(177 citation statements)
references
References 62 publications
(92 reference statements)
9
167
0
1
Order By: Relevance
“…Nipponbare, WT) and transgenic plants overexpressing OsPIN2 (OX1 and OX2) were used in this study. Transgenic rice seeds (Chen et al , 2012) were kindly provided by Xu Guohua from Nanjing Agricultural University, China. Seeds of WT, OX1, and OX2 were surface sterilized for 30min in a 10% (v/v) H 2 O 2 solution, washed with deionized water, soaked in deionized water at 30 °C overnight, then germinated at 30 °C in darkness for 2 d. The germinated seeds were transferred to a net floating on a 0.5 mmol l –1 CaCl 2 solution (pH 4.5) for 3 d.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nipponbare, WT) and transgenic plants overexpressing OsPIN2 (OX1 and OX2) were used in this study. Transgenic rice seeds (Chen et al , 2012) were kindly provided by Xu Guohua from Nanjing Agricultural University, China. Seeds of WT, OX1, and OX2 were surface sterilized for 30min in a 10% (v/v) H 2 O 2 solution, washed with deionized water, soaked in deionized water at 30 °C overnight, then germinated at 30 °C in darkness for 2 d. The germinated seeds were transferred to a net floating on a 0.5 mmol l –1 CaCl 2 solution (pH 4.5) for 3 d.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpressing OsPIN2 can enhance auxin transport from shoot to root and auxin polar transport in roots (Chen et al , 2012). Acid-growth theory indicates that auxin can activate plasma membrane (PM) H + -ATPase and facilitate H + efflux into the cell wall compartment, thus softening the cell wall and initiating extension growth (Hager, 2003; Grebe, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Loss of function of LAZY1 enhanced polar auxin transport (PAT) and impaired lateral auxin transport, resulting in reduced shoot gravitropism and a tiller-spreading phenotype . Suppressing the expression of rice PIN-FORMED1 or enhancing that of rice PIN-FORMED2, two auxin efflux transporters, both altered PAT and increased tiller angles (Xu et al, 2005;Chen et al, 2012). Additionally, many quantitative trait loci (QTLs) affecting tiller angle have been identified (Li et al, 1999).…”
mentioning
confidence: 99%
“…Plants that spread too much shade their neighbors and thereby reduce grain production per unit area, whereas those that are too upright are susceptible to insect pests and pathogens because of increased contact with other plants and higher humidity within the clump. Several proteins have been identified that control tiller angle, including PROSTRATE GROWTH1 (PROG1) (Jin et al 2008;Tan et al 2008), LOOSE PLANT ARCHITECTURE 1 (LPA1) (Wu et al 2013), LAZY1 , and PIN-FORMED2 (Chen et al 2012;Xu et al 2005). The latter two proteins regulate auxin transport, whereas the mechanism of PROG1 influence is unknown.…”
Section: Stemsmentioning
confidence: 98%